1994
DOI: 10.1111/j.1365-2494.1994.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on milk production of feeding silage and sugar‐beet pulp as separate components, in a mixed ration or as an ensiled blend

Abstract: Twenty early‐lactation British Friesian dairy cows were used in a five‐treatment, partially balanced change‐over design experiment, consisting of four periods each of 4 weeks' duration. Three treatments consisted of offering ensiled blends of silage and sugar‐beet pulp produced by mixing 40 (S40), 80 (S80) and 120 (S120)kg beet pulp t−1 herbage at ensiling. In two further treatments, an untreated silage was supplemented with 5 kg of beet pulp daily, either mixed with the silage prior to feeding (SM) or offered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Various experiments have evaluated the effect of adding sugar beet pulp ( Offer and Al‐Rwidah, 1989a; b; Ferris and Mayne, 1994a ; b; c) or rolled barley ( Jones et al ., 1990 ) to grass silages in order to reduce ensiling losses. These studies showed that the addition of MSBP or barley to grass silages reduced ensiling losses, and the reduction was mainly due to the reduced DM losses associated with effluent flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various experiments have evaluated the effect of adding sugar beet pulp ( Offer and Al‐Rwidah, 1989a; b; Ferris and Mayne, 1994a ; b; c) or rolled barley ( Jones et al ., 1990 ) to grass silages in order to reduce ensiling losses. These studies showed that the addition of MSBP or barley to grass silages reduced ensiling losses, and the reduction was mainly due to the reduced DM losses associated with effluent flow.…”
Section: Discussionmentioning
confidence: 99%
“…The relative merits of feeding MSBP ensiled with grass silage or as a separate feed are inconsistent between experiments both with dairy cows ( Dulphy and Demarquilly, 1975; Ferris and Mayne, 1994a; b; c) and with beef cattle ( Jones and Jones, 1988 ; O’Kiely, 1990; Moore and Kennedy, 1994). The addition of MSBP might improve the balance of nutrients available to the rumen microbes, providing readily available sugars in addition to starch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Moseley and Ramanathan () reported increased DM and metabolizable energy intake by sheep of mixed perennial ryegrass and white clover silage prepared with the addition of either 25 g/kg rolled barley or sugar beet pulp (Moseley & Ramanathan, ). In contrast, when beet pulp was incorporated in the silo, it decreased energy intake and digestible organic matter of the grass silage (Ferris & Mayne, ) as well as weight gain of growing cattle (Moore & Kennedy, ) compared to when it was offered either separately or as a component mixed with the silage before feeding.…”
Section: Introductionmentioning
confidence: 99%